A new species and a new record of Pero Herrich-Schäffer, 1855 (Lepidoptera, Geometridae) in the Andes of southern Peru - Carlos Palacios; Jackie Farfán; José Cerdeña; Ana Lazo-Rivera; Luis E. Parra; Héctor A. Vargas (Nota Lepidopterologica, 2020)
Two species of the moth genus Pero Herrich-Schäffer, 1855 (Lepidoptera, Geometridae, Ennominae, Odontoperini) are added to the fauna of the Andes of southern Peru in the Arequipa Department. Pero lopezi Vargas & Palacios sp. nov. is described and illustrated based on male adults collected in Pocsi, at 2900 m elevation. Pero atridisca Dognin, 1906, previously known from Angasmarca (La Libertad), is recorded for the first time in Arequipa, significantly expanding its distribution range.